Atomization and droplet dynamics of a gas-liquid two-phase jet under different mass loading ratios. (June 2022) - Wu, Hao; Zhang, Fujun; Zhang, Zhenyu; Hou, Lin
Highlights: The mass load ratio shows a significant impact on droplet transport characteristics of gas-liquid two-phase jets. The droplets with a diameter less than 5 μm follow the gas flow faithfully and can be used to estimate the local gas flow velocity. The equilibrium position of droplet breakup and coalescence in the gas-liquid jet is calculated and found to be quite close to the nozzle exit. Droplet collision outcomes and the possibility of various outcomes based on previous studies are quantified. Abstract: Atomization and droplet dynamics of a gas-liquid two-phase jet were investigated experimentally, with the particular interest in the influence of mass loading ratio (the ratio of droplet mass flow rate to the carrier-phase mass flow rate, ranging from 0.60 to 3.23) on the jet atomization. Droplet size and velocity at selected positions were obtained by employing Phase Doppler Particle Analyzer (PDPA), combined with backlit illumination for spray visualization. Droplet transport characteristics are substantially influenced by the mass load ratio. Characterization of the local gas flow velocity by using droplets smaller than 5 μ m reveals a highly turbulent jet with Reynolds number exceeding 5 × 10 4, implying the possibility of droplet turbulent breakup. Critical equilibrium location x c r i t between droplet breakup and coalescence is close to the nozzle exit and a positive correlation is found between mass loading ratio and x c r i t . Exaltation of mass loading ratio increases the droplet size and decreases the velocity. Quantification of droplet collision outcome indicates a relatively high probability of coalescence, which explicates the downstream increasing of measured droplet Sauter mean diameter along the centerline of far-field jet.